2019
DOI: 10.1161/hypertensionaha.118.11780
|View full text |Cite
|
Sign up to set email alerts
|

Apneic Sleep, Insufficient Sleep, and Hypertension

Abstract: These changes progressively increase from lighter to deeper stages of NREM, i.e. sleep stages N1 through N3. BP, HR, cardiac output and peripheral vascular resistance all decrease in NREM stages 1 through 3 10,11 . Thus, BP normally shows a "dipping" pattern at night 12 . REM sleepIn rapid eye movement (REM) sleep, there is a reduction in tone of the respiratory muscles except for the diaphragm 13 . Simultaneously, a decrease in sensitivity of the central chemoreceptors occurs 14 . Consequently, ventilation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 238 publications
0
36
0
Order By: Relevance
“…The relationship between obesity, OSA, and HTN has been well studied in adult patients and demonstrates independent relationships amongst the comorbidities 10,12 . The relationship has not been as well studied in pediatric patients; while some prior studies demonstrate that these comorbidities often exist in adolescent patients, 21–23 there is no study that confirms a clear, independent relationship between OSA and HTN, as it does in adult patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between obesity, OSA, and HTN has been well studied in adult patients and demonstrates independent relationships amongst the comorbidities 10,12 . The relationship has not been as well studied in pediatric patients; while some prior studies demonstrate that these comorbidities often exist in adolescent patients, 21–23 there is no study that confirms a clear, independent relationship between OSA and HTN, as it does in adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…While there is an established relationship amongst OSA, obesity, and HTN/EBP, the relative contributions of obesity and OSA individually to the development of HTN/EBP remain unclear. In adults, it has been shown that OSA is the second most prevalent contributor to HTN/EBP after obesity 10–12 . However, the relationship between HTN/EBP and OSA is not clearly established in adolescents 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea is known to be accompanied by elevated blood pressure and increased blood pressure variability (Mansukhani, Covassin, & Somers, 2019;Narkiewicz et al, 1998), while the association between PLMS and hypertension is less compelling (Koo, Sillau, Dean, Lutsey, & Redline, 2015;Walters & Rye, 2009). However, in our patients we did not observe appreciable differences between nighttime and daytime blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of treatment of OSA in lowering BP is modest, with a reduction in mean 24-h SBP and DBP of approximately 2–4 mm Hg (20, 86). The BP lowering effects of CPAP are noted in subjects with pre-hypertension and hypertension, and appear to be greater in those with a higher number of hours of device usage and those who are sleepy, comorbid diabetes mellitus, and possibly in those using fixed vs. auto-titrating modes of PAP (87, 88). Studies have suggested that CPAP treatment may reverse non-dipping of BP at night in those with resistant hypertension (89, 90).…”
Section: Sleep Apnea and Hypertensionmentioning
confidence: 99%